2020
DOI: 10.1177/1533033820909911
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells and Fibronectin 1 in the Prognosis of Nasopharyngeal Carcinoma

Abstract: Objective: Nasopharyngeal carcinoma is highly endemic in Southeast China. Circulating tumor cell is an important biomarker in the prognosis of variety kinds of cancers. Overexpression of fibronectin 1 was observed in variety kinds of malignancies and may contribute to progress and metastasis of the cancers. The current study was aimed to investigate phenotypes of circulating tumor cell in nasopharyngeal carcinoma blood and fibronectin 1 expression in the circulating tumor cell, and their clinical application i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Studies have found that low FN1 expression was associated with prolonged survival in diffuse, poorly differentiated, and node-positive gastric cancer [44,45]. Further, the expression level of FN1 has also been shown to be abnormally elevated in ovarian cancer [46], nasopharyngeal carcinoma [47], and other tumors and is considered a marker of poor prognosis. Versican is encoded by the VCAN gene and is not only a large chondroitin sulfate proteoglycan but also a major component of the ECM.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that low FN1 expression was associated with prolonged survival in diffuse, poorly differentiated, and node-positive gastric cancer [44,45]. Further, the expression level of FN1 has also been shown to be abnormally elevated in ovarian cancer [46], nasopharyngeal carcinoma [47], and other tumors and is considered a marker of poor prognosis. Versican is encoded by the VCAN gene and is not only a large chondroitin sulfate proteoglycan but also a major component of the ECM.…”
Section: Discussionmentioning
confidence: 99%
“…CTC are tumor cells that detach from the primary or metastatic focus of the tumor and enter the blood ( 38 ). In recent years, CTC has been used as an important prognostic marker for many solid tumors, including lung cancer ( 39 ), breast cancer ( 40 ), prostate cancer ( 41 ), nasopharyngeal cancer ( 42 ), rectal cancer ( 43 ), and so on. CTC detection can effectively make up for the deficiency of imaging, serum markers, and tissue samples in the evaluation of the prognosis of patients with gastric cancer, providing qualitative, specific, and dynamic evaluation, and avoiding temporal and spatial heterogeneity of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In nasopharyngeal carcinoma, Zhang [ 18 ] found that after 2–4 cycles of chemotherapy, the CTC count of NPC was reduced remarkably, and the change in CTC number was correlated with treatment response. Qian [ 19 ] reported that the reduction of CTC was related to the treatment effect of patients with advanced NPC, and the positive CTC before treatment was an independent risk factor for poor prognosis. Yu [20] reported that CTC was associated with poor survival in NPC patients, which may be an independent prognostic factor affecting NPC.…”
Section: Discussionmentioning
confidence: 99%